(untitled) - Cragg, Claudia (London, 1995)
The New Taipans is a vital sourcebook on the people and business of the Asian Pacific region based on knowledge gathered by the author over a fifteen year period. Take the reader into a closed and privileged word, a word where the asian Dream was conceived and realized, and provides details of the economics culture and business philosophy.
Keywords: Businessmen,Doanh nhân; Asia, Southeastern,Đông Nam Á